Examining the Impact of Promotions, CRM, and Consumer Trust on Customer Loyalty Through Consumer Satisfaction: A Path Analysis Study on English Center Students - Yucha, Nikma; Hwihanus, Hwihanus (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research aims to examine the influence of promotions, CRM, and consumer trust on customer loyalty through consumer satisfaction as an intervening variable. Research was conducted on consumers who were students at the English Center. The sample collection method in this research was a simple random sampling technique of 159 respondents. The research analysis method used is path analysis. The results of this research are direct, namely that promotion has a positive and significant effect on consumer satisfaction. CRM has a positive and insignificant effect on consumer satisfaction. Consumer trust has a positive and significant effect on consumer satisfaction. The promotion has a positive and negligible effect on consumer loyalty. CRM has a negative and insignificant effect on consumer loyalty. Consumer trust has a positive and significant effect on consumer loyalty. and consumer satisfaction has a positive and significant effect on consumer loyalty. Meanwhile, the indirect research results are that promotions positively and significantly affect consumer loyalty through consumer satisfaction. CRM has a positive and insignificant effect on consumer loyalty through consumer satisfaction. Consumer trust positively and significantly affects consumer loyalty through consumer satisfaction.